2014
DOI: 10.3852/13-298
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering species boundaries in theCeratocystis paradoxacomplex, including a new species from oil palm and cacao in Cameroon

Abstract: Abstract:The Ceratocystis paradoxa complex accommodates a group of fungal pathogens that have become specialized to infect mostly monocotyledonous plants. Four species currently are recognized in this group, including C. paradoxa, which has a widespread distribution and broad host range. In this study, multigene phylogenetic analyses involving sequences of the ITS, b-tubulin and TEF-1a gene loci, in combination with phenotypic and mating studies, were used to characterize purported C. paradoxa isolates from Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 36 publications
2
60
0
6
Order By: Relevance
“…Henry (1944) described conidia in the range of 4-22 × 2-4.5 µm, whereas in this study the size range of conidia from his specimen (BPI 595712) was 4-8.5 × 2-3 µm. Bretz's (1952) description of conidia reflected a mixture of endogenous conidia and aleurioconidia (see Mbenoun et al 2014), described as 'thick-walled, olivaceous to brown, polymorphic spores, 3.5-5.5 µm wide to 5 to 20 µm long, formed endogenously and intercalarily in hyphae, which may also produce hyaline endoconidia'. We observed only hyaline, endogenous conidia in the range of 3-6.5 × 2-3 µm from the Bretz specimen (FP 97476).…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Henry (1944) described conidia in the range of 4-22 × 2-4.5 µm, whereas in this study the size range of conidia from his specimen (BPI 595712) was 4-8.5 × 2-3 µm. Bretz's (1952) description of conidia reflected a mixture of endogenous conidia and aleurioconidia (see Mbenoun et al 2014), described as 'thick-walled, olivaceous to brown, polymorphic spores, 3.5-5.5 µm wide to 5 to 20 µm long, formed endogenously and intercalarily in hyphae, which may also produce hyaline endoconidia'. We observed only hyaline, endogenous conidia in the range of 3-6.5 × 2-3 µm from the Bretz specimen (FP 97476).…”
Section: Morphologymentioning
confidence: 99%
“…Endoconidiophora was confined to species previously treated in the C. coerulescens complex, with E. coerulescens as the type species. Based on the phylogenies presented by Mbenoun et al (2014) and De Beer et al (2014), Thielaviopsis with T. ethacetica as the type species, included species previously treated in the C. paradoxa complex. Consequently, none of the four genera (Ceratocystis, Endoconidiophora, Thielaviopsis or Chalara) are available to accommodate C. fagacearum, which resides in a lineage distinct from these genera .…”
Section: Introductionmentioning
confidence: 99%
“…Genera in this family typically exhibit a wide variety of sexual reproductive strategies, including heterothallism as employed by Davidsoniella eucalypti (KILE et al 1996), primary homothallism as seen in Thielaviopsis cerberus (MBENOUN et al 2014) and homothallism via unidirectional mating type switching as observed in Ce.…”
Section: Introductionmentioning
confidence: 99%
“…Some species are heterothallic, such as T. ethacetica and T. paradoxa s. str., other species are homothallic, such as T. cerberus (Mbenoum et al 2014). The sexual state of T. musarum was described by Riedl (1962) but no ascospores were observed, and the mating system was not determined (Mbenoum et al 2014).…”
mentioning
confidence: 94%
“…De Beer & W.C. Allen, T. cerberus and representatives of T. paradoxa s. lat. (Mbenoum et al 2014). Undiscovered species of the T. paradoxa complex are likely to exist in Brazil, mainly due to the large number of records of this fungus associated with various plant species (Mendes et al 1998).…”
mentioning
confidence: 99%